1996
DOI: 10.1038/hdy.1996.42
|View full text |Cite
|
Sign up to set email alerts
|

Parental effects in Plantago lanceolata L. II. Manipulation of grandparental temperature and parental flowering time

Abstract: In an experimental study of Plantago lanceolata L., postzygotic environmentally induced parental effects were (1) transmitted across generations, (2) genotype-specific, and (3) mediated by natural differences in flowering phenology. Individuals were cloned, hand-pollinated and allowed to mature seed at one of two temperatures. Second-generation plants were induced to seed-set at four times during the flowering season. The effects of grandparental temperature (GPT), parental flowering time (PFT) and maternal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…In one such study, adaptive transgenerational effects of drought remained after effects of provisioning were removed via covariate analysis, confirming that the expression of transgenerational plasticity in this system relies on additional mechanisms [24]. Studies in other plant systems have also identified effects of parental environment that are independent of seed provisioning [67][68][69], suggesting that other regulatory mechanisms may be involved in many cases of transgenerational plasticity in plants.…”
Section: Discussion (A) Dna Methylation Mediates Adaptive Transgeneramentioning
confidence: 79%
“…In one such study, adaptive transgenerational effects of drought remained after effects of provisioning were removed via covariate analysis, confirming that the expression of transgenerational plasticity in this system relies on additional mechanisms [24]. Studies in other plant systems have also identified effects of parental environment that are independent of seed provisioning [67][68][69], suggesting that other regulatory mechanisms may be involved in many cases of transgenerational plasticity in plants.…”
Section: Discussion (A) Dna Methylation Mediates Adaptive Transgeneramentioning
confidence: 79%
“…This fact was particularly evident in several studies carried out with Plantago lanceolata [Plantaginaceae] (Lacey et al 1997). While temperature effects on germination are mediated by the seed coat, the embryo mediates other, more persistent, effects of temperature on parental effects (Case et al 1996).…”
Section: Seed Coat: Origin Structures and Characteristicsmentioning
confidence: 99%
“…Transgenerational effects of environmental variation on adult phenotypes, mediated by maternal effects, have been observed in some plants (Miao et al 1991;Case et al 1996; reviews in Roach and Wulff 1987;Bernardo 1996a) but are particularly well documented in animals in which progeny spend a substantial amount of time during development inside of their mother (e.g., mammals, many aphids) or in which parental care is provided after progeny are born or hatched (Riska et al 1985;Cheverud and Moore 1994). However, the persistence of environmental variation across generations appears to be uncommon in animals that lay eggs immediately after fertilization, in which progeny complete development entirely outside of their mother, without parental care (i.e., most animals).…”
mentioning
confidence: 99%